EFFECTIVENESS OF DIGESTIVE SYSTEM PROBLEM-BASED INTERACTIVE E-MODULE IN IMPROVING STUDENT CONCEPT MASTERY - Yuliani, Yuyun; Djarot, Prasetyorini (Universitas Pakuan, 2023)
This research was conducted to determine the effectiveness of teaching materials in the form of problem-based interactive E-Modules. Prior to conducting this research, a preliminary study was carried out which consisted of literature studies and field studies. This type of research is experimental research. The data collection instruments were in the form of interview sheets to analyze the effectiveness of the teacher's needs and questionnaires to analyze the effectiveness of the E-Module on students as well as concept mastery tests in the form of pretest and posttest which were given to the control class and the experimental class. The interactive e-module used contains text, images and learning videos as an independent learning effort arranged in an experimental class. The subject of this study used 2 classes of students in class XI MIPA SMA YPHB, amounting to 30 people each. The results of the control class research resulted in an N-gain value of 0.37 in the medium category and the experimental class produced an N-Gain value of 0.66 in the moderate category so that it can be concluded that the use of problem-based interactive E-Module has a moderate effect on student mastery of concepts.